An exhaustive analysis of post-traumatic brain injury dementia using bibliometric methodologies - Sang, Xian-Zheng; Wang, Cheng-Qing; Chen, Wen; Rong, Hong; Hou, Li-Jun (Frontiers in Neurology, 2023)
Background It is widely accepted that traumatic brain injury (TBI) increases the risk of developing long-term dementia, although some controversies surrounding this topic exist. Annually, approximately 69 million individuals suffer from TBI all around the world. Such a large population of TBI patients could lead to a future surge in the number of dementia patients. Due to the potentially severe consequences of TBI, various research projects on post-TBI dementia have emerged worldwide. Therefore, it is essential to comprehend the current status and development of post-TBI dementia for future research. Objective The purpose of the study was to provide an overview of the field and identify hotspots, research frontiers, and future research trends for post-TBI dementia. Methods Articles related to post-TBI dementia were retrieved from the Web of Science Core Collection for the period between 2007 and 2022, and analyzing them based on factors such as citations, authors, institutions, countries, journals, keywords, and references. Data analysis and visualization were conducted using VOSviewer, CiteSpace, and an online bibliometric platform (https://bibliometric.com). Results From 2007 to 2022, we obtained a total of 727 articles from 3,780 authors and 1,126 institutions across 52 countries, published in 262 journals. These articles received a total of 29,353 citations, citing 25,713 references from 3,921 journals. Over the last 15 years, there has been a significant upward trend in both publications and citations. The most productive country was the United States, the most productive institution was Boston University, and the most productive author was McKee AC. Journal of Neurotrauma has been identified as the periodical with the greatest number of publications. Three clusters were identified through cluster analysis of keywords. A burst in the use of the term “outcome” in 2019 is indicative of a future research hotspot. The timeline view of references showed 14 clusters, of which the first 4 clusters collected the majority of papers. The first 4 clusters were “chronic traumatic encephalopathy,” “age of onset,” “tauopathy,” and “cognitive decline,” respectively, suggesting some areas of interest in the field. Conclusion The subject of post-TBI dementia has raised much interest from scientists. Notably, America is at the forefront of research in this area. Further collaborative research between different countries is imperative. Two topical issues in this field are “The association between TBI and dementia-related alterations” and “chronic traumatic encephalopathy (CTE).” Studies on clinical manifestation, therapy, pathology, and pathogenic mechanisms are also popular in the field.